دور المؤسسة العسكرية في صنع قرارات السياسة الخارجية - سالم أ.أحمد المرغني; عقل أ.عامر علي (Aljameai, 2022)
الملخص: النخبة هي مجموعة من الافراد الذين يمتلكون خصائص معينة لا يمتلكها بالمقابل الافراد الاخرين، ويضم المجتمع بدوره مجموعة من النخب التي تقود مؤسساته سواء كانت منها السياسية او الاقتصادية او العسكرية او الاجتماعية، فأما الحديث عن نخب القيادات في السلطة، فيمكن القول بأن النخبة السياسية والتي هي مجموعة الافراد الذين يمتلكون مصادر وادوات التأثير السياسي في عملية رسم السياسة العامة وصنع القرارات الرئيسة في المجتمع، وتضم قيادات المؤسسات الرسمية وغير الرسمية، وهناك مجموعة قليلة من الافراد تشكل النخبة السياسية، تمارس دورا رئيساً في هذا المجال، وينسحب مفهوم النخبة على العديد من المؤسسات التي تشكل هيكل الدولة، فبالنسبة للقاعدة الشعبية نجد ان النخب الحزبية والتي هي مجموعة منظمة من الافراد لها هدف محدد وهو استلام السلطة عن طريق الحصول على دعم القاعدة الشعبية في الانتخابات، ويتضمن الترويج لبرامجها الحزبية والرؤية التي تقدمها في إدارة الدولة للمرحلة المقبلة، ويدخل ضمن إطار القيادات الفاعلة النخب العسكرية التي يكون لها دور فعال في الدول التي تكثر فيها الانقلابات العسكرية أو التي تتعرض إلى تهديدات خارجيه، أو التي بنيت هياكل مؤسساتها اصلا وفق القاعدة العسكرية عن طريق وصول الجنرالات إلى سلم السلطة السياسية، ويساعد في إدارة شؤون الدولة وتنظيمها مجموعه من الموظفين الذين يطلق عليهم البيروقراطيين ،حيث أن النخب البيروقراطية يكون لها دور أساسي في إدارة شؤون الدولة، علاوة على الدور الاجتماعي الذي تقوم به النخب الاخرى من قبيل النخب الاقتصادية والاجتماعية والدينية والمثقفة، فالنخب الاقتصادية تلعب دورا أساسياً في البلدان التي تنتهج اقتصاد السوق والمبدأ الرأسمالي، حيث أن النخب التي تمتلك رؤوس الأموال والمصانع تكون شريكة في صنع القرار داخل أروقة المجالس التشريعية، وأما النخب الدينية فتزداد فاعلية وقوة النخب الدينية بقدر ما يقوى إيمان الأفراد الديني وتديّنهم، كما بقدر ما يفرض النظام السياسي التوجه الديني العام بطريق معين، فيكبر دور نخبة رجال الدين في المجتمع والسلطة، ولا يخفى علينا دور النخب المثقفة الذين اختلفت تحليلات المفكرين حول دورهم، فمنهم من وضع النخبة المثقفة كموظفين لدى الجماعة المسيطرة، ومنهم عكس ذلك، ففي بعض المجتمعات يصبح المثقفون أقرب ما يكونوا إلى الصفوة الحاكمة. Abstract: Elite is a group of individuals who possess certain properties not owned by contrast, other individuals, and includes community turn a group of Elites who lead institutions, whether including political, economic or military or social, either talking about the Elite leaders in power it can be said that the political Elite, which is individuals who own sources and tools of political influence in the process of policy-making and making key decisions in the community group, and includes the leaders of both formal and informal institutions, and there are a few groups of individuals constitute that political Elite, exert a major role in this area, and applies the concept of Elite, many of the institutions that form the structure of the state, for the popular base we find tha getting the popular base support in the elections, including the promotion of their party and the vision provided by the state Administration for the next stage, and falls within the framework of the leaders active military Elites who have an active role in the countries that abound in military coups or exposed to external threats, or wich institutions structures originally built according to the military base, by the arrival of the generals to the ladder of political power, and helps in the management of the affairs of state and organized a group of staff who are called bureaucrats is the Elite bureaucracy have a key role in state institutions management, as well as the social role played by other Elites such as economic, social, religious and educated Elites economic Elites play a key role in countries that market and the principle of the capitalist economy, where the Elites who owns the money heads and factories be a partner in the decision within the corridors of legislatures making and the religious Elites will become more effective and power of. of both formal and informal institutions, and there are a few groups of individuals constitute that political Elite, exert a major role in this area, and applies the concept of Elite, many of the institutions that form the structure of the state, for the popular base we find tha getting the popular base support in the elections, including the promotion of their party and the vision provided by the state Administration for the next stage, and falls within the framework of the leaders active military Elites who have an active role in the countries that abound in military coups or exposed to external threats, or wich institutions structures originally built according to the military base, by the arrival of the generals to the ladder of political power, and helps in the management of the affairs of state and organized a group of staff who are called bureaucrats is the Elite bureaucracy have a key role in state institutions management, as well as the social role played by other Elites such as economic, social, religious and educated Elites economic Elites play a key role in countries that market and the principle of the capitalist economy, where the Elites who owns the money heads and factories be a partner in the decision within the corridors of legislatures making and the religious Elites will become more effective and power.